1994
DOI: 10.1099/0022-1317-75-6-1407
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the helper component protease gene of zucchini yellow mosaic virus affect its ability to mediate aphid transmissibility

Abstract: The nucleotide sequence of the helper component protease (HC-Pro) genes of three zucchini yellow mosaic virus (ZYMV) strains has been compared with that of a helper-deficient strain of ZYMV-HC. The comparisons revealed three unique deduced amino acid differences. Two of these mutations were located in regions which are conserved in other potyviruses. The role of these mutations in aphid transmissibility was examined by exchanging DNA fragments of part of the deficient HCPro gene with the respective section wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 30 publications
0
74
0
2
Order By: Relevance
“…The N-terminal portion of HC-Pro is required for aphidmediated plant-to-plant transmission (Atreya et al, 1992;Atreya & Pirone, 1993). However, in a recent report a point mutation within the conserved C-terminal proline-threonine-lysine (PTK) box of HC-Pro was shown to be associated with loss of aphid transmissibility of zucchini yellow mosaic potyvirus (Granier et al, 1993;Huet et al, 1994), suggesting that more than one site in HC-Pro could be involved in aphid transmission activity.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal portion of HC-Pro is required for aphidmediated plant-to-plant transmission (Atreya et al, 1992;Atreya & Pirone, 1993). However, in a recent report a point mutation within the conserved C-terminal proline-threonine-lysine (PTK) box of HC-Pro was shown to be associated with loss of aphid transmissibility of zucchini yellow mosaic potyvirus (Granier et al, 1993;Huet et al, 1994), suggesting that more than one site in HC-Pro could be involved in aphid transmission activity.…”
Section: Introductionmentioning
confidence: 99%
“…The S7G substitution in CP (which reduced virus accumulation) restored transmissibility to PVA-B11 (no plants infected of the 40 plants inoculated), as shown by transmission of B11-DAG (11\20) and B11-U CP (5\10) to a rate similar to PVA-U (6\10). The motifs within HC-Pro required for aphidtransmissibility in other potyviruses (Atreya & Pirone, 1993 ;Huet et al, 1994) are conserved in PVA-B11 (Puurand et al, 1994 ;Rajama$ ki et al, 1998). The requirement of the CP Nterminal DAG motif for aphid-transmissibility has been proven in four other potyviruses by mutational analysis of the icDNA clones (Atreya et al, 1991 ;Gal-On et al, 1992 ;Flasinski et al, 1996 ;Lo!…”
Section: Bbdfmentioning
confidence: 99%
“…The N-terminal part of HC-Pro affects virulence (symptom severity), genome amplification and virus accumulation (Atreya et al, 1992 ;Atreya & Pirone, 1993 ;Kasschau & Carrington, 1995). KITC and PTK amino acid motifs of HC-Pro are required for transmissibility by aphid vectors (Atreya & Pirone, 1993 ;Huet et al, 1994). The central region of HC-Pro affects long-distance movement of virus (Cronin et al, 1995), whereas the C-terminal part is needed for cell-to-cell movement Author for correspondence : Jari Valkonen (at Department of Plant Biology, Uppsala).…”
Section: Introductionmentioning
confidence: 99%
“…For another ZYMV isolate, two mutations were found between the HAT and PAT strains, one of them occurring in a conserved cluster of amino-acids Pro-Thr-Lys (PTK) (Granier et al, 1993). Huet et al (1994) modified the PTK of ZYMV to PAK in an infectious cDNA clone and observed a total loss of HC activity in aphid transmission. An aminoacid exchange (R to I) in another conserved box (the FRNK box) resulted in more than 50% reduction in aphid transmission, but did not completely abolish transmission (Huet et al, 1994).…”
Section: Aphid Transmissionmentioning
confidence: 99%
“…Huet et al (1994) modified the PTK of ZYMV to PAK in an infectious cDNA clone and observed a total loss of HC activity in aphid transmission. An aminoacid exchange (R to I) in another conserved box (the FRNK box) resulted in more than 50% reduction in aphid transmission, but did not completely abolish transmission (Huet et al, 1994).…”
Section: Aphid Transmissionmentioning
confidence: 99%